Pattern of Uveitis in Saudi Female Patients in Western Region of Saudi Arabia - Nizamuddin S. Mohammad; Ahmed B. Bawazeer (Journal of King Abdulaziz University: Medical Sciences, 2023)
The purpose of this study is to determine the pattern of uveitis in Saudi female patients in the western region of Saudi Arabia. Retrospective analysis of the records of patients with uveitis referred to uveitis clinics in Maghraby Eye Hospital and in King Abdulaziz University Hospital, Jeddah, Saudi Arabia, showed 124 female Saudi patients among 519 patients with uveitis out of 50,000 new cases from 1999-2008. The native Saudi patients constituted 50% of total patients (260/519). Acute idiopathic anterior uveitis was found to be 61 (49%) among 124 patients. There were 14 patients (10.3%) of Vogt-Koyanagi-Harada syndrome, 10 cases (8%) of Toxoplasmosis, 7 patients (5.6%) of Behçet’s disease, and 6 patients (4.8%) of Fuchs’ heterochromic iridocyclitis. Anterior uveitis was found to be 58.8% of total cases, panuveitis 21.4%, posterior uveitis 11.2%, and intermediate uveitis 8%. In conclusion, the most common cause of uveitis among Saudi female patients was idiopathic anterior uveitis followed by Vogt-Koyanagi-Harada syndrome, Toxoplasmosis and Behçet’s disease. The most common cause of posterior uveitis was Toxoplasmosis. The most common cause for panuveitis was found to be Vogt-Koyanagi-Harada syndrome.